The Influence of Visionary Leadership on Employee Performance at the Department of Industry and Trade of Gowa Regency - Amalia, Nur; Rizaldi, Andi Risfan; Nurinaya (Jurnal Economic Resource, 2025)
The purpose of this study was to determine the effect of visionary leadership on employee performance at the Industry and Trade Office of the Gowa Regency. The sample in this study amounted to 39 people. The type of data used in this research is quantitative data. Data collection was carried out by means of observation and distributing questionnaires. The data sources used in data collection are primary data and secondary data. The results showed that visionary leadership had a positive and significant effect on employee performance at the Industry and Trade Office of Gowa Regency. This shows that the more effective the application of visionary leadership, the better employee performance will be.